Does the Technique of Skin Closure Affect the Cosmesis of Cervical Thyroidectomy and Parathyroidectomy Scars? A Review of Literature - Mahalingam, Sridhayan; Alatsatianos, Anton; Pitkin, Lisa; D'Souza, Alwyn (Facial Plastic Surgery, 2018)
The cosmetic outcomes following thyroid and parathyroid surgery is a priority for patients as the surgical scar is in a visible area of the body. Although some have advocated the use of minimally invasive and robotic surgery, these are not without risks and it has been suggested that the scars are not necessarily more favorable. The three most common means of skin closure include the use of subcuticular sutures, clips, and tissue adhesive (with or without deeper subcutaneous sutures) and there are no previous reviews of the published evidence. In this study, the authors compare the cosmetic outcomes through a systematic review of literature. Three studies (n = 200) comparing subcuticular sutures and clips suggest superior cosmetic outcomes with sutures (with statistically significant differences in the immediate postoperative period). Three studies (n = 213) comparing sutures and tissue adhesive show superior outcomes with sutures in the early postoperative period with no differences thereafter. Two studies (n = 202) comparing tissue adhesive and clips do not show that one is superior to the other and show no significant differences. Overall the data are limited; however, the evidence suggests that subcuticular sutures may offer superior cosmetic outcomes than clips and tissue adhesive in conventional thyroid and parathyroid surgery.
Keywords: thyroidectomy; cervicotomy; scar